16.4: Novel SFT Mode Pixel Design for High Viewing Angle of Contrast at Automotive Applications. (28th November 2018) - Zhou, Jun; Ding, Zong-cai; Chen, Jiang-chuan; Wang, Jian-hong; Zhang, Yu; Li, Jun
Abstract : Customers will concern about different optical parameters in different display applications. Mobile phone displays focused on high transmittance rates, the higher transmittance rates, the lower cost and power consumption. Automotive displays focused on viewing angle of contrast, especially at horizontal direction, because the CID is at the center of driver and co‐driver. Therefore, the applications of SFT mode display change from mobile phone to automotive, the pixel design changes from vertical 2‐domain to horizontal 2‐domain.Tianma proposes a novel SFT mode pixel design, which adopts fake horizontal 2‐domain and stretches the Common ITO space to the boundary of Source line. Compared to the traditional design and high contrast ratio design, the novel pixel design can improve both the contrast ratio and transmittance rates about 20%.